Analysis Model of Pedestrian Facilities as a Support for Sustainable Transportation System in Jakarta - Bawono, Bagas Dwi; Mudjanarko, Sri Wiwoho; Safarizki, Hendramawat Aski (LPPM of NAROTAMA UNIVERSITY, 2025)
Jakarta, with its various urban challenges, requires integrated solutions. Transportation issues are one of the most crucial aspects to address. The interaction between its various elements must be carefully planned, one of which is pedestrian infrastructure. This study aims to analyze the role of pedestrian facilities as an integral part of the sustainable transportation system in Jakarta, identify related problems, and develop a pedestrian facility model that supports the use of sustainable transportation modes. Using a qualitative descriptive method, this study applies Partial Least Squares-Structural Equation Modeling (PLS-SEM) to evaluate the relationship between pedestrian infrastructure conditions and public preference in using environmentally friendly transportation modes. The infrastructure issues in Jakarta regarding carbon emission reduction, urban mobility enhancement, and the integration of pedestrian planning with technological advancements, such as autonomous vehicles, are discussed. Data were collected through surveys and literature studies. The analysis results on the relationship and influence of pedestrian facility models on the sustainable transportation system show that Model B (technology-based pedestrian facilities) has a t-statistic value of 7.863 and a P-value of 0.000, which is significantly higher than Model A (social-based pedestrian facilities) with a t-statistic value of 3.259 and a P-value of 0.001. The analysis of pedestrian facility models on user satisfaction shows similar results, where Model B has a t-statistic of 7.863 and a P-value of 0.000, compared to Model A's t-statistic of 3.259 and a P-value of 0.001. This conclusion indicates that technology-based pedestrian facilities are more favored by users.